Positive pole piece, secondary battery and electric device

By adopting a multi-layer film structure in the positive electrode sheet of a lithium-ion battery and adjusting the specific surface area and carbon content of the active material, the problem of the positive electrode sheet becoming brittle is solved, and the processing performance and cycle life of the battery are improved.

CN119852305AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202410175809.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2025-04-18
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

The positive electrode of a lithium-ion battery is prone to the problem of the electrode brittleness after cold pressing, which leads to cracking and falling off of the active material during subsequent striping, cutting and winding, which seriously affects the processing performance, electrochemical performance and safety performance of the battery.

Method used

A positive electrode sheet including a positive electrode current collector and a positive electrode film layer is adopted. The positive electrode film layer consists of a first positive electrode film layer and a second positive electrode film layer. The first positive electrode film layer includes a first positive electrode active material, and the second positive electrode film layer includes a second positive electrode active material. By adjusting the specific surface area and carbon content of the active material, the flexibility of the electrode sheet is improved.

Benefits of technology

The good flexibility of the positive electrode sheet is achieved, and the processing performance, electrochemical performance and safety performance of the battery are improved. The battery containing the positive electrode sheet of the present application has a high energy density and a long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852305A_ABST
    Figure CN119852305A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a secondary battery and an electric device. Particularly, the invention provides the positive pole piece, the positive pole piece comprises a positive pole current collector and positive pole film layers, the positive pole film layers are arranged on at least one surface of the positive pole current collector, the positive pole film layers comprise a first positive pole film layer and a second positive pole film layer, and the first positive pole film layer is located between the positive pole current collector and the second positive pole film layer; wherein the first positive electrode film layer comprises a first positive electrode active material, the specific surface area of the first positive electrode active material is 12 m < 2 > / g-16 m < 2 > / g, the carbon content of the first positive electrode active material is 1.0 wt%-1.5 wt% based on the total weight of the first positive electrode active material, the second positive electrode film layer comprises a second positive electrode active material, the specific surface area of the second positive electrode active material is 6 m < 2 > / g-19 m < 2 > / g, and the carbon content of the second positive electrode active material is 1.0 wt%-1.5 wt% based on the total weight of the second positive electrode active material. Based on the total weight of the second positive electrode active material, the carbon content of the second positive electrode active material is 1.1 wt%-2.1 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high operating voltage, long cycle life, light weight, and no environmental pollution. Therefore, they have become an ideal power source for small and lightweight electronic devices such as cameras, mobile phones, laptops, digital products, etc., and are also the preferred power source for future high-energy power batteries in automobiles.

[0003] Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, separators and electrolytes. In the production of lithium-ion batteries, the positive and negative electrode slurries are first coated on the corresponding current collectors, dried and cold pressed, and then the subsequent processes are carried out. Due to the characteristics of the positive electrode active materials (for example, lithium iron phosphate salts, lithium manganese iron phosphate salts, etc.), the positive electrode is prone to become brittle after cold pressing. In the subsequent stripping and cutting process, the active materials may crack and fall off, and the pole pieces may also break during the winding process, which seriously affects the processing performance, electrochemical performance and safety performance of the battery.

[0004] Therefore, it is necessary to provide a positive electrode plate having good plate flexibility. Summary of the invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode plate, a secondary battery and an electrical device, wherein the positive electrode plate has good plate flexibility.

[0006] The inventors have discovered that the above objectives can be achieved by adopting the technical solution of the present invention.

[0007] The first aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer is arranged on at least one side of the positive electrode current collector, the positive electrode film layer comprises a first positive electrode film layer and a second positive electrode film layer, wherein the first positive electrode film layer is located between the positive electrode current collector and the second positive electrode film layer, wherein

[0008] The first positive electrode film layer comprises a first positive electrode active material, and the specific surface area of ​​the first positive electrode active material is 12 m 2 / g-16m 2 / g, based on the total weight of the first positive electrode active material, the carbon content of the first positive electrode active material is 1.0 wt %-1.5 wt %,

[0009] The second positive electrode film layer comprises a second positive electrode active material, and the specific surface area of ​​the second positive electrode active material is 6 m 2 / g-19m 2 / g, based on the total weight of the second positive electrode active material, the carbon content of the second positive electrode active material is 1.1 wt%-2.1 wt%.

[0010] The positive electrode plate of the present application has good electrode plate flexibility.

[0011] In any embodiment, the compaction density of the first positive electrode active material is 2.4-2.7 g / cm when measured at 3T pressure. 3 .

[0012] When the compaction density of the first positive electrode active material is 2.4-2.7 g / cm 3 When the positive electrode plate of the present application is used, the battery has a higher energy density.

[0013] In any embodiment, the first positive electrode active material comprises first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, the first lithium iron phosphate salt particles have a primary average particle size of 50-300 nm, and the second lithium iron phosphate salt particles have a primary average particle size of 400-500 nm.

[0014] In any embodiment, based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles, the number of the first lithium iron phosphate salt particles accounts for 60%-80%, and the number of the second lithium iron phosphate salt particles accounts for 20%-40%.

[0015] In any embodiment, the second positive electrode active material comprises third lithium iron phosphate salt particles, and a ratio of a withholding capacity C2 of the third lithium iron phosphate salt particles at 60° C. to a withholding capacity C1 of the third lithium iron phosphate salt particles at 25° C. is C2 / C1≥1.02.

[0016] When C2 / C1≥1.02, the positive electrode plate of the present application has a higher compaction density, and the battery containing the positive electrode plate of the present application has a longer cycle life, a lower capacity attenuation degree and a higher cycle climbing degree.

[0017] In any embodiment, the carbon content of the second positive electrode active material is 1.2 wt % to 2 wt % based on the total weight of the second positive electrode active material.

[0018] When the carbon content of the second positive electrode active material is 1.2 wt %-2 wt %, the battery including the positive electrode sheet of the present application has a good balance between cycle life and gram capacity.

[0019] In any embodiment, a ratio W1 / W2 of a weight W1 of the first positive electrode active material to a weight W2 of the second positive electrode active material is 1:9 to 9:1.

[0020] In any embodiment, a ratio W1 / W2 of a weight W1 of the first positive electrode active material to a weight W2 of the second positive electrode active material is 3:7 to 7:3.

[0021] When W1 / W2 is 3:7 to 7:3, the positive electrode plate of the present application has a higher compaction density, and the battery containing the positive electrode plate of the present application has a higher cycle climbing degree.

[0022] In any embodiment, the thickness of the first positive electrode film layer and the thickness of the second positive electrode film layer are independently 5-80 μm.

[0023] The second aspect of the present application provides a secondary battery, which includes the positive electrode sheet of the first aspect of the present application.

[0024] A third aspect of the present application provides an electrical device, which includes the secondary battery of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the first positive electrode active material in Example 1 of the present application at a magnified size of 10k.

[0026] Figure 2 This is a scanning electron microscope image of the second positive electrode active material in Example 1 of the present application at a magnified size of 10k.

[0027] Figure 3 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0028] Figure 4 yes Figure 3 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0029] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.

[0030] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0031] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0032] Figure 8 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0033] Description of reference numerals:

[0034] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION

[0035] Below, the embodiments of the positive electrode plate, secondary battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0036] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0039] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0040] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0041] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0042] Lithium-ion batteries are mainly composed of a positive electrode, a negative electrode, a separator and an electrolyte. In the manufacture of lithium-ion batteries, the positive and negative electrode slurries are first coated on the corresponding current collectors, dried and cold pressed, and then the subsequent processes are carried out. Due to the characteristics of the positive electrode active materials (for example, lithium iron phosphate salts, lithium manganese iron phosphate salts, etc.), the positive electrode is prone to become brittle after cold pressing. In the subsequent stripping and cutting process, the active materials may crack and fall off. The problem of the pole piece may also occur during the winding process, which seriously affects the processing performance, electrochemical performance and safety performance of the battery. Therefore, it is necessary to provide a positive electrode pole piece with good pole piece flexibility.

[0043] Based on this, the present application proposes a technical solution to solve the above technical problems.

[0044] The first aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer is arranged on at least one side of the positive electrode current collector, the positive electrode film layer comprises a first positive electrode film layer and a second positive electrode film layer, wherein the first positive electrode film layer is located between the positive electrode current collector and the second positive electrode film layer, wherein

[0045] The first positive electrode film layer comprises a first positive electrode active material, and the specific surface area of ​​the first positive electrode active material is 12 m 2 / g-16m 2 / g, based on the total weight of the first positive electrode active material, the carbon content of the first positive electrode active material is 1.0 wt %-1.5 wt %,

[0046] The second positive electrode film layer comprises a second positive electrode active material, and the specific surface area of ​​the second positive electrode active material is 6 m 2 / g-19m 2 / g, based on the total weight of the second positive electrode active material, the carbon content of the second positive electrode active material is 1.1 wt%-2.1 wt%.

[0047] When the above conditions are met, the surface of the second positive electrode active material in the second positive electrode film layer has a higher carbon coating amount, which can effectively reduce the sliding resistance between the particles, and the particles between the positive electrode materials are easier to slide. Furthermore, under the same electrode sheet compaction conditions, the particles are easier to slide and less likely to break, thereby improving the flexibility of the electrode sheet, so that the positive electrode sheet of the present application has better electrode sheet flexibility.

[0048] In some embodiments, based on the total weight of the first positive electrode active material, the carbon content of the first positive electrode active material is Cx1 weight %, wherein a ratio z1 of a specific surface area of ​​the first positive electrode active material to Cx1 satisfies 10≤z1≤13.

[0049] In some embodiments, based on the total weight of the second positive electrode active material, the carbon content of the second positive electrode active material is Cx2 weight %, wherein a ratio z2 of the specific surface area of ​​the second positive electrode active material to Cx2 satisfies 6≤z2≤11.

[0050] When the above conditions are met, the degree of graphitization of the surface carbon coating is high, the interlayer slip force is small, and under the same electrode compaction conditions, the particles are easier to slide and less likely to break, so that the positive electrode of the present application has better electrode flexibility.

[0051] In some embodiments, z1 can be 10, 10.3, 11, 11.5, 12, 12.3, 12.5, 13, or a range consisting of any two of the above z1 values ​​or a value within the range.

[0052] In some embodiments, z2 can be 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, or a range consisting of any two of the above z2 values ​​or a value within the range.

[0053] In the present application, the term "specific surface area" or "BET" refers to the total external surface area per unit weight of a positive electrode active material.

[0054] The specific surface area BET can be measured by methods and equipment known in the art. For example, it can be measured using Tristar 3020 with reference to GB / T 19587-2004.

[0055] In some embodiments, the specific surface area of ​​the first positive electrode active material is 12.3 m 2 / g-15.6m 2 / g.

[0056] In some embodiments, the specific surface area BET of the first positive electrode active material may be 12 m 2 / g, 12.3m 2 / g, 13m 2 / g, 13.2m 2 / g, 13.5m 2 / g, 14m 2 / g, 14.4m 2 / g, 14.5m 2 / g, 15m 2 / g, 15.5m 2 / g, 15.6m 2 / g, 16m 2 / g, or is a range composed of the BET specific surface areas of any two of the above-mentioned first positive electrode active materials or a value within the range.

[0057] If the BET of the first positive electrode active material is too high, it will increase the water absorption performance, affect the processing performance of the slurry and increase the side reaction with the electrolyte. However, if the BET of the first positive electrode active material is too low, the gram capacity will be reduced. The BET of the first positive electrode active material is controlled at 12m 2 / g-16m 2 / g, which helps to obtain better slurry processing performance and gram capacity, thereby improving the processing problems of the battery cell and controlling the side reactions with the electrolyte within an acceptable range, thereby improving the volume energy density of the battery and the battery cell life.

[0058] In some embodiments, the specific surface area of ​​the second positive electrode active material is 6.6 m 2 / g-19m 2 / g.

[0059] In some embodiments, the specific surface area BET of the second positive electrode active material may be 6 m 2 / g, 6.5m 2 / g, 6.6m 2 / g, 7m 2 / g, 7.2m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.5m2 / g, 9m 2 / g, 9.5m 2 / g, 9.9m 2 / g, 10m 2 / g, 10.5m 2 / g, 10.8m 2 / g, 11m 2 / g, 11.5m 2 / g, 12m 2 / g, 12.5m 2 / g, 12.6m 2 / g, 13m 2 / g, 13.2m 2 / g, 13.5m 2 / g, 14m 2 / g, 14.4m 2 / g, 14.5m 2 / g, 15m 2 / g, 15.5m 2 / g, 16m 2 / g, 16.5m 2 / g, 17m 2 / g, 17.5m 2 / g, 18m 2 / g, 18.5m 2 / g, 19m 2 / g, or a range consisting of the BET specific surface areas of any two of the above-mentioned second positive electrode active materials or a value within the range.

[0060] If the BET of the second positive electrode active material is too high, it will increase the water absorption performance, affect the processing performance of the slurry and increase the side reaction with the electrolyte. However, if the BET of the second positive electrode active material is too low, the gram capacity will be reduced. Control the BET of the second positive electrode active material to 6m 2 / g-19m 2 / g, which helps to obtain better slurry processing performance and gram capacity, thereby improving the processing problems of the battery cell. At the same time, it can also adjust the initial capacity of the second active material and then adjust the degree of slow attenuation.

[0061] The carbon content of the first positive electrode active material / the second positive electrode active material can be measured by methods and equipment known in the art. For example, it can be tested by infrared absorption method after combustion in a high-frequency induction furnace according to GB / T 20123-2006 / ISO.

[0062] In some embodiments, the carbon content of the first positive electrode active material is Cx1 wt % based on the total weight of the first positive electrode active material, wherein 1.0≤Cx1≤1.5.

[0063] If the carbon content of the first positive electrode active material is too high, it will affect the insertion and extraction of lithium ions, and affect the gram capacity of the battery to a certain extent. However, if the carbon content of the first positive electrode active material is too low, it will affect the conductivity of the battery, which is not conducive to its kinetic performance. Controlling the carbon content of the first positive electrode active material between 1.0 wt% and 1.5 wt% helps to obtain better kinetic performance and gram capacity. The carbon content in this weight percentage range can take into account the conductive network between the active material particles without affecting the capacity, and can play a lubricating role between the particles, thereby achieving high kinetics and high energy density.

[0064] In some embodiments, Cx1 is 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, or a range of Cx1 compositions of any two of the first positive electrode active materials or a value within the range.

[0065] In some embodiments, the carbon contained in the first positive electrode active material is coated on the surface of its particles. In some embodiments, the carbon contained in the first positive electrode active material is embedded in its particles. In some embodiments, the carbon contained in the first positive electrode active material is partially coated on the surface of its particles and partially embedded in its particles.

[0066] In some embodiments, the carbon content of the second cathode active material is 1.1 wt %-2.1 wt % based on the total weight of the second cathode active material. In some embodiments, the carbon content of the second cathode active material is 1.2 wt %-2 wt % based on the total weight of the second cathode active material.

[0067] Too high a carbon content of the second positive electrode active material will affect the insertion and extraction of lithium ions, and to a certain extent affect the gram capacity of the battery. However, too low a carbon content of the second positive electrode active material will affect the cycle life of the battery. When the carbon content of the second positive electrode active material is controlled at 1.2 wt%-2 wt%, while ensuring that the material has a slow decay effect, the reduction in initial capacity can be compensated by using it in conjunction with the first active material, thereby achieving slow decay while taking into account energy density, so that the battery containing the positive electrode plate of the present application has a good balance between cycle life and gram capacity.

[0068] In some embodiments, Cx2 is 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, or a range of Cx2 compositions of any two of the second positive electrode active materials or a value within the range.

[0069] In some embodiments, the carbon contained in the second positive electrode active material is coated on the surface of its particles. In some embodiments, the carbon contained in the second positive electrode active material is embedded in its particles. In some embodiments, the carbon contained in the second positive electrode active material is partially coated on the surface of its particles and partially embedded in its particles.

[0070] In some embodiments, the compaction density of the first cathode active material is 2.4-2.7 g / cm when measured at 3T pressure. 3 In some embodiments, the compaction density of the first cathode active material is 2.43-2.63 g / cm when measured at 3T pressure. 3 .

[0071] When the compaction density of the first positive electrode active material is 2.4-2.7 g / cm 3 When the volume is constant, a higher compaction density can place more active materials in a unit volume, thereby improving the energy density, so that the battery containing the positive electrode plate of the present application has a higher energy density.

[0072] In some embodiments, the first positive electrode active material comprises first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, the first lithium iron phosphate salt particles have a primary average particle size of 50-300 nm, and the second lithium iron phosphate salt particles have a primary average particle size of 400-500 nm.

[0073] With the above-mentioned particle size combination, under the same pressure conditions, the electrode pores are smaller, thereby achieving high compaction density and improving energy density.

[0074] In some embodiments, based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles, the number of the first lithium iron phosphate salt particles accounts for 60%-80%, and the number of the second lithium iron phosphate salt particles accounts for 20%-40%.

[0075] The quantity distribution of particles of the above-mentioned particle sizes can also reduce the porosity of the pole pieces under the same pressure conditions, thereby increasing the compaction density and energy density.

[0076] In the present application, the term "primary average particle size" refers to the average value of the primary particle sizes of all particles, wherein the primary particle size refers to the longest distance connecting two points on the edge in a cross-sectional view.

[0077] The primary average particle size of the first lithium iron phosphate salt particle / the second lithium iron phosphate salt particle can be measured by methods and equipment known in the art. For example, it can be tested by scanning electron microscopy and long diameter statistical method. As an example, a sample is tested with a ZEISS sigma 300 scanning electron microscope, and then tested with reference to standard JY / T010-1996 to observe the sample morphology. The morphology of the primary particles is observed, and particles of any 10 regions with the same size and shape in the same scanning electron microscope image (SEM) at a magnification of 10k are observed. The 10 regions are then divided into 5 positions, including the four corners and the center. The Feret diameter of any primary particle at each position under the magnification is selected, and the Feret diameter results of the 5 positions including the four corners and the center are averaged to obtain the diameter of the primary particles in the region. The diameters of the primary particles obtained in the 10 regions are then compared and counted to obtain the distribution ratio (quantity ratio) of the diameters of the primary particles. The diameters of the primary particles obtained in the 10 regions are averaged to obtain the average diameter of the primary particles (i.e., the primary average diameter). Specifically, the average value of the four dimensions, namely, the dimension of the particle in the direction of the two adjacent sides of the rectangle circumscribed with the image and the dimension in the direction of the 45-degree inclination of the two adjacent sides of the rectangle circumscribed with the image, is set as the Feret diameter of the particle.

[0078] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles may be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, or a range consisting of any two of the foregoing primary average particle sizes or a value within the range.

[0079] In some embodiments, the primary average particle size of the second lithium iron phosphate salt particles can be 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm, 500nm, or a range consisting of any two of the above primary average particle sizes or a value in the range.

[0080] In some embodiments, the second positive electrode active material comprises third lithium iron phosphate salt particles, and a ratio of a withholding capacity C2 of the third lithium iron phosphate salt particles at 60° C. to a withholding capacity C1 of the third lithium iron phosphate salt particles at 25° C. is C2 / C1≥1.02.

[0081] When C2 / C1≥1.02, the capacity of the active material cannot be fully utilized at the beginning of the battery cycle. During the continuous cycle of the battery, along with the activation of the active material, the capacity is gradually utilized, thereby extending the capacity retention rate at the beginning of the battery cycle. Therefore, when C2 / C1≥1.02, the positive electrode sheet of the present application has a higher compaction density, and the battery containing the positive electrode sheet of the present application has a longer cycle life, a lower capacity attenuation degree, and a higher cycle climbing degree.

[0082] The method for measuring the buckle capacitance of the third lithium iron phosphate salt particles is as follows:

[0083] When measuring the button capacity of the third lithium iron phosphate salt particles, first prepare a button battery: mix the third lithium iron phosphate salt particles, the adhesive polyvinylidene fluoride (PVDF), and the conductive agent acetylene black in a weight ratio of 95:5:5, add an appropriate amount of N-methylpyrrolidone (NMP) solvent, and stir and mix thoroughly to form a uniform positive electrode slurry; apply this slurry on an aluminum foil with a thickness of 1μm for the positive electrode collector, then dry and cold press it, and then punch it into small discs with a diameter of 14mm as the positive electrode. Use a lithium sheet as the negative electrode, use a 12μm thick polypropylene isolation film and a common lithium iron phosphate electrolyte, and assemble it into a button battery. Then,

[0084] For the button capacity C2 of the third lithium iron phosphate salt particles at 60°C: At 60°C, charge and discharge at a rate of 0.1C and record the corresponding gram capacity. The test conditions are as follows: At 60°C, let the button battery stand for 3 hours, charge to the upper cutoff voltage (3.75V) at a constant current of 0.1C, then charge to 50μA at a constant voltage, let stand for 5 minutes, and record the charging capacity of the button battery. The charging gram capacity C2 of the third lithium iron phosphate salt particles at 60°C = the charging capacity of the button battery at 60°C / the weight of the third lithium iron phosphate salt particles in the button battery.

[0085] For the button capacity C2 (i.e., gram capacity) of the third lithium iron phosphate salt particles at 25°C: at 25°C, charge and discharge at a rate of 0.1C and record the corresponding gram capacity. The test conditions are as follows: at 25°C, let the button battery stand for 3 hours, charge to the upper cutoff voltage (3.75V) at a constant current of 0.1C, then charge to 50μA at a constant voltage, let stand for 5 minutes, and record the charge capacity of the button battery. The charge gram capacity C1 of the third lithium iron phosphate salt particles at 25°C = the charge capacity of the button battery at 25°C / the weight of the third lithium iron phosphate salt particles in the button battery.

[0086] In some embodiments, C2 / C1 can be 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, or a range consisting of any two of the above C2 / C1 or a value within the range.

[0087] In some embodiments, the primary average particle size of the third lithium iron phosphate salt particles can be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, or a range consisting of any two of the above primary average particle sizes or a value within the range.

[0088] The method for measuring the primary average particle size of the third lithium iron phosphate salt particles may be the same as the method for measuring the primary average particle size of the first lithium iron phosphate salt particles.

[0089] In some embodiments, the Dv50 of the third lithium iron phosphate salt particles can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, or a range consisting of any two of the above Dv50 or a value within the range.

[0090] Dv50 can be measured by methods and equipment known in the art. For example, it can be measured with reference to GB / T19077-2016 / ISO13320:2009 using a laser particle size analyzer (Malvern Master Size 3000). The specific test process is as follows: Take an appropriate amount of the sample to be tested, and the sample concentration is guaranteed to be 8% to 12% shading. Add 20mL of deionized water, and ultrasonically control it for 5min at the same time, with an ultrasonic frequency of 53KHz and an ultrasonic power of 120W to ensure that the sample is completely dispersed, and then measure the sample according to the GB / T19077-2016 / ISO13320:2009 standard.

[0091] In some embodiments, a ratio W1 / W2 of a weight W1 of the first positive electrode active material to a weight W2 of the second positive electrode active material is 1:9 to 9:1.

[0092] In some embodiments, a ratio W1 / W2 of a weight W1 of the first positive electrode active material to a weight W2 of the second positive electrode active material is 3:7 to 7:3.

[0093] When W1 / W2 is 3:7 to 7:3, the first active material layer ensures the energy density of the battery, and the second active material layer optimizes the flexibility of the battery pole piece while providing a slow decay effect. Therefore, when W1 / W2 is 3:7 to 7:3, the positive pole piece of the present application has a higher compaction density, and the battery containing the positive pole piece of the present application has a higher cycle climbing degree.

[0094] In some embodiments, the thickness of the first positive electrode film layer and the thickness of the second positive electrode film layer are independently 5-80 μm. In some embodiments, the thickness of the first positive electrode film layer and the thickness of the second positive electrode film layer are independently 8-72 μm. In some embodiments, the thickness of the first positive electrode film layer and the thickness of the second positive electrode film layer are independently 24-56 μm. In some embodiments, the thickness of the first positive electrode film layer and the thickness of the second positive electrode film layer are independently 30-50 μm. In some embodiments, the thickness of the first positive electrode film layer and the thickness of the second positive electrode film layer are independently 5μm, 8μm, 10μm, 15μm, 16μm, 20μm, 24μm, 25μm, 30μm, 32μm, 35μm, 40μm, 45μm, 48μm, 50μm, 55μm, 56μm, 60μm, 64μm, 65μm, 70μm, 72μm, 75μm, 80μm, or a range consisting of any two of the above thicknesses or a value in the range.

[0095] The second aspect of the present application provides a secondary battery, which includes the positive electrode sheet of the first aspect of the present application.

[0096] A third aspect of the present application provides an electrical device, which includes the secondary battery of the second aspect of the present application.

[0097] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0098] In one embodiment of the present application, a secondary battery is provided.

[0099] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0100] [Positive electrode]

[0101] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0102] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0103] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0104] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0105] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0106] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0107] [Negative electrode]

[0108] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0109] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0110] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0111] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0112] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0113] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0114] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0115] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0116] [Electrolytes]

[0117] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0118] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0119] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0120] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0121] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0122] [Isolation film]

[0123] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0124] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0125] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0126] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0127] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0128] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example.

[0129] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0130] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0131] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0132] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0133] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0134] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0135] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0136] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0137] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0138] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0139] Example

[0140] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0141] 1. Preparation method

[0142] Example 1

[0143] 1) Preparation of positive electrode active materials and positive electrode slurry

[0144] The preparation method of the first positive electrode active material is as follows: ferrous oxalate and lithium dihydrogen phosphate (weight ratio 1:2) are used as raw materials, polyethylene glycol is used as a carbon source, the weight of the carbon source accounts for 17% of the total weight of the raw materials (ferrous oxalate + lithium dihydrogen phosphate + polyethylene glycol), 2000ppm TiO2 (based on the total weight of the raw materials) is added as an additive, the particle size Dv50 is ground to 0.4μm by a sand mill, and then spray-dried, and the outlet temperature is controlled at 150°C to obtain a spherical dried material. The spherical dried material is sintered in a nitrogen atmosphere, and the potting amount is controlled to be 5kg, the nitrogen flow rate is 300L / min, the heating rate is 3°C / min, the sintering temperature is 780°C, and the constant temperature section is 12h to obtain a sintered material. The sintered material was pulverized by air flow with a classifier frequency of 50 Hz using an air flow mill to obtain the first positive electrode active material, and the primary particle size of each particle was measured. For particles with a primary particle size of ≤350 nm, the number and average particle size of the first lithium iron phosphate salt particles were counted and the average particle size was calculated; for particles with a primary particle size of >350 nm, the number and average particle size of the second lithium iron phosphate salt particles were counted and the average particle size was calculated. Based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles, the primary average particle size of the first lithium iron phosphate salt particles was 150 nm, accounting for 70% of the total number, and the primary average particle size of the second lithium iron phosphate salt particles was 450 nm, accounting for 30% of the total number.

[0145] The first positive electrode active material, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black were mixed in a weight ratio of 97.3:2:0.7, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added and fully stirred to form a uniform first positive electrode slurry with a viscosity of 6000 mPa·s.

[0146] The preparation method of the second positive electrode active material is as follows: iron phosphate and lithium carbonate are used as raw materials, and glucose and polyethylene glycol are added as carbon sources in a weight ratio of 7:3, and the weight of the carbon source accounts for 17% of the total weight of the raw materials. The above iron phosphate: lithium carbonate: carbon source is mixed in a weight ratio of 3.85:1:1 and wet-grinded with water as a solvent. The Dv50 of the slurry after grinding is 300nm. The obtained slurry is spray-dried and then sintered in a roller furnace. It is sintered at 760℃ for 24h. Nitrogen is introduced during the sintering process, and the heating rate is 3℃ / min. Then it is naturally cooled to a material temperature of <80℃ and then discharged to obtain a calcined material. The calcined material is subjected to air flow crushing, screening, demagnetization and vacuum packaging. The frequency of the classifier of the air flow crushing is controlled to be 80Hz and the frequency of the induced draft fan is controlled to be 40Hz to obtain a second positive electrode active material, wherein the primary average particle size of the third lithium iron phosphate salt particles is 400nm and Dv50 is 0.7μm.

[0147] The second positive electrode active material, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black were mixed in a weight ratio of 97.3:2:0.7, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added and fully stirred to form a uniform second positive electrode slurry with a viscosity of 6000 mPa·s.

[0148] 2) Preparation of positive electrode

[0149] The first positive electrode slurry was coated on a 15 μm thick aluminum foil with a coating weight of 160 mg / 1540.25 cm 2 , and then dried to form the first positive electrode film layer. The specific surface area of ​​the first positive electrode active material is 13.2m 2 / g, the carbon content of the first positive electrode active material is Cx1 weight %, wherein Cx1 is 1.2, and the ratio of the specific surface area of ​​the first positive electrode active material to Cx1 is z1=12.

[0150] The second positive electrode slurry is coated on the first positive electrode film layer, and the coating weight is 160 mg / 1540.25 cm 2 , and then dried to form a second positive electrode film layer. The specific surface area of ​​the second positive electrode active material is 10.8m 2 / g, the carbon content of the second positive electrode active material is Cx2 weight %, wherein Cx2 is 1.8, and the ratio of the specific surface area of ​​the second positive electrode active material to Cx2 is z2=6.

[0151] The aluminum foil, the first positive electrode film layer and the second positive electrode film layer together form the positive electrode sheet.

[0152] 3) Preparation of negative electrode sheet

[0153] The negative electrode active material graphite, thickener sodium carboxymethyl cellulose, adhesive styrene butadiene rubber, and conductive agent acetylene black are mixed in a weight ratio of 97:1:1:1, and deionized water is added to obtain negative electrode slurry under the action of a vacuum mixer. The negative electrode slurry is evenly coated on a copper foil with a thickness of 8μm. Subsequently, it is dried, cold pressed, and slit to obtain a negative electrode sheet.

[0154] 4) Preparation of electrolyte

[0155] Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were prepared into a mixed solution in a volume ratio of 20:20:60, and then fully dried lithium salt was dissolved in the mixed solution, and then 10wt% of fluoroethylene carbonate additive was added and mixed evenly to obtain an electrolyte. The concentration of the lithium salt was 1mol / L. The entire operation process was carried out in an argon atmosphere glove box with a water content of <10ppm.

[0156] 5) Isolation film

[0157] A polyethylene film with a thickness of 12 μm was used as the separator.

[0158] 6) Preparation of batteries

[0159] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with a prepared electrolyte, and packaged, injected, formed, and vented to obtain a lithium-ion battery.

[0160] Example 2

[0161] The difference between Example 2 and Example 1 is that the specific surface area of ​​the first positive electrode active material is 14.4, so the ratio of the specific surface area of ​​the first positive electrode active material to Cx1 is z1=12.

[0162] Example 3

[0163] The difference between Example 3 and Example 1 is that the specific surface area of ​​the first positive electrode active material is 15.6, so the ratio of the specific surface area of ​​the first positive electrode active material to Cx1 is z1=13.

[0164] Example 4

[0165] The difference between Example 4 and Example 1 is that the ratio of the withheld capacity C2 of the third lithium iron phosphate salt particles at 60°C to the withheld capacity C1 of the third lithium iron phosphate salt particles at 25°C is C2 / C1=1.04, the specific surface area of ​​the second positive electrode active material is 14.4, and thus the ratio of the specific surface area of ​​the second positive electrode active material to Cx2 is z2=8.

[0166] Example 5

[0167] The difference between Example 5 and Example 1 is that: C2 / C1=1.025, the specific surface area of ​​the second positive electrode active material is 18m 2 / g, the specific surface area of ​​the second positive electrode active material=18, so the ratio of the specific surface area of ​​the second positive electrode active material to Cx2 is z2=10.

[0168] Example 6

[0169] The difference between Example 6 and Example 1 is that: C2 / C1=1.02.

[0170] Example 7

[0171] The difference between Example 7 and Example 1 is that the specific surface area of ​​the second positive electrode active material is 7.2 m 2 / g, the carbon content is Cx2 weight%, where Cx2 is 1.2.

[0172] Example 8

[0173] The difference between Example 8 and Example 1 is that the specific surface area of ​​the second positive electrode active material is 12 m 2 / g, the carbon content is Cx2 weight %, where Cx2 is 2.

[0174] Example 9

[0175] The difference between Example 9 and Example 1 is that the specific surface area of ​​the second positive electrode active material is 6.6 m 2 / g, the carbon content is Cx2 weight%, where Cx2 is 1.1.

[0176] Example 10

[0177] The difference between Example 10 and Example 1 is that the specific surface area of ​​the second positive electrode active material is 12.6 m 2 / g, the carbon content is Cx2 weight%, where Cx2 is 2.1.

[0178] Embodiment 11

[0179] The difference between Example 11 and Example 1 is that: the primary average particle size of the first lithium iron phosphate salt particles is 300nm, and the number accounts for 60% (based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles), and the primary average particle size of the second lithium iron phosphate salt particles is 400nm, and the number accounts for 40% (based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles); in addition, the ratio W1 / W2 of the weight W1 of the first positive electrode active material to the weight W2 of the second positive electrode active material is 1:9 (the total weight of the first positive electrode active material and the second positive electrode active material is the same as in Example 1).

[0180] Example 12

[0181] The difference between Example 12 and Example 1 is that the primary average particle size of the first lithium iron phosphate salt particles is 50 nm, accounting for 80% of the number (based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles), and the primary average particle size of the second lithium iron phosphate salt particles is 500 nm, accounting for 20% of the number (based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles); in addition, W1 / W2 is 9:1 (the total weight of the first positive electrode active material and the second positive electrode active material is the same as in Example 1).

[0182] Example 13

[0183] The difference between Example 13 and Example 1 is that W1 / W2 is 3:7 (the total weight of the first positive electrode active material and the second positive electrode active material is the same as that in Example 1).

[0184] Embodiment 14

[0185] The difference between Example 14 and Example 1 is that W1 / W2 is 7:3 (the total weight of the first positive electrode active material and the second positive electrode active material is the same as that in Example 1).

[0186] Embodiment 15

[0187] The difference between Example 15 and Example 1 is that W1 / W2 is 1:9 (the total weight of the first positive electrode active material and the second positive electrode active material is the same as that in Example 1).

[0188] Example 16

[0189] The difference between Example 16 and Example 1 is that W1 / W2 is 9:1 (the total weight of the first positive electrode active material and the second positive electrode active material is the same as that in Example 1).

[0190] Embodiment 17

[0191] The difference between Example 17 and Example 1 is that: C2 / C1=1.01; the specific surface area of ​​the second positive electrode active material is 19m 2 / g, so z2 is 10.5.

[0192] Embodiment 18

[0193] The difference between Example 18 and Example 1 is that the specific surface area of ​​the first positive electrode active material is 12.3 m 2 / g, the carbon content is Cx1 weight %, where Cx1 is 1, and thus z1 is 12.3.

[0194] Embodiment 19

[0195] The difference between Example 19 and Example 1 is that the specific surface area of ​​the first positive electrode active material is 15.5 m 2 / g, the carbon content is Cx1 weight %, where Cx1 is 1.5, and thus z1 is 10.3.

[0196] Comparative Example 1

[0197] The difference between Comparative Example 1 and Example 1 is that the second positive electrode film layer is not included, and the aluminum foil and the first positive electrode film layer are combined to form the positive electrode sheet.

[0198] Comparative Example 2

[0199] The difference between Comparative Example 2 and Example 2 is that the second positive electrode film layer is not included, and the aluminum foil and the first positive electrode film layer are combined to form the positive electrode sheet.

[0200] Comparative Example 3

[0201] The difference between Comparative Example 3 and Example 3 is that the second positive electrode film layer is not included, and the aluminum foil and the first positive electrode film layer are combined to form the positive electrode sheet.

[0202] 2. Battery performance test

[0203] 1) Primary average particle size

[0204] The samples were tested using a ZEISS sigma 300 scanning electron microscope, and then tested according to standard JY / T010-1996 to observe the sample morphology.

[0205] The morphology of the primary particles is observed, and particles of the same size and shape in any 10 regions in the same scanning electron microscope image (SEM) at a magnification of 10k are observed. The 10 regions are then subdivided into 5 positions, including the four corners and the center, and the Feret particle size of any primary particle at each position under this magnification is selected, and the Feret particle size results of the 5 positions including the four corners and the center are averaged to obtain the particle size of the primary particles in this region, and then the particle sizes of the primary particles obtained in the 10 regions are compared and counted to obtain the distribution ratio (quantity ratio) of the particle size of the primary particles; the particle sizes of the primary particles obtained in the 10 regions are averaged to obtain the average particle size of the primary particles (i.e., the primary average particle size). Specifically, the average value of the four sizes of the particle in the direction of the two adjacent sides of the rectangle circumscribed with the image and the size in the direction of the 45-degree inclination of the two adjacent sides of the rectangle circumscribed with the image is set as the Feret particle size of the particle.

[0206] 2) Dv50

[0207] The laser particle size analyzer Malvern 3000 (MasterSizer 3000) was used for measurement with reference to the standard process: GB / T19077-2016 / ISO13320:2009.

[0208] The specific test process is as follows: take an appropriate amount of the sample to be tested, and ensure that the sample concentration is 8% to 12% shading. Add 20mL of deionized water and ultrasonicate for 5 minutes at a frequency of 53KHz and a power of 120W to ensure that the sample is completely dispersed. Then, measure the sample according to the GB / T19077-2016 / ISO13320:2009 standard.

[0209] 3) Specific surface area

[0210] The specific surface area was determined in accordance with the standard GB / T 19587-2004 using Tristar 3020 as the testing instrument.

[0211] 4) Carbon content

[0212] The determination of carbon content follows the standard GB / T 20123-2006 / ISO and is tested using the infrared absorption method after combustion in a high-frequency induction furnace.

[0213] 5) Compacted density:

[0214] Powder compaction density

[0215] A certain amount of powder is placed on a special compaction mold with a known diameter, with a metal sheet on each side of the mold, and the powder is placed in the middle. By applying pressure (3T pressure) and testing the corresponding powder thickness at the same time, the corresponding powder volume is obtained. The compaction density ρ is calculated using the formula ρ=m / v. The specific operation can be carried out in accordance with the standard: GB / T24533-2009.

[0216] Pole compaction density

[0217] Cut the electrode into 1000mm long films; roll the positive electrode under a certain pressure. Due to the ductility of aluminum foil, the film length is 1006mm, and the punching length is 1540.25mm. 2 By measuring the weight and thickness of the small disc, the compacted density can be calculated.

[0218] 6) 60℃ / 25℃ buckling capacity

[0219] The third lithium iron phosphate salt particles, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are mixed in a weight ratio of 95:5:5, and an appropriate amount of N-methylpyrrolidone (NMP) solvent is added, and the mixture is stirred and mixed to form a uniform positive electrode slurry; the slurry is coated on an aluminum foil with a thickness of 1 μm for the positive electrode current collector, and then dried and cold pressed, and then punched into small discs with a diameter of 14 mm as the positive electrode. The lithium sheet is used as the negative electrode, and a 12 μm thick polypropylene isolation film and a common lithium iron phosphate electrolyte are used to assemble a button cell. At 60℃ / 25℃, charge and discharge at a rate of 0.1C and record the corresponding gram capacity.

[0220] The test conditions are as follows: at 25°C, the button cell is allowed to stand for 3 hours, charged to the upper cutoff voltage (3.75V) at a constant current of 0.1C, then charged to 50μA at a constant voltage, allowed to stand for 5 minutes, and the charging capacity of the button cell is recorded. The charging gram capacity of the third lithium iron phosphate salt particles at 25°C C1 = the charging capacity of the button cell at 25°C / the weight of the third lithium iron phosphate salt particles in the button cell. At 60°C, the button cell is allowed to stand for 3 hours, charged to the upper cutoff voltage (3.75V) at a constant current of 0.1C, then charged to 50μA at a constant voltage, allowed to stand for 5 minutes, and the charging capacity of the button cell is recorded. The charging gram capacity of the third lithium iron phosphate salt particles at 60°C C2 = the charging capacity of the button cell at 60°C / the weight of the third lithium iron phosphate salt particles in the button cell.

[0221] 7) Cycle life test

[0222] 1. The battery is left at 20°C for 120 minutes.

[0223] 2.1C discharge to 2.5V

[0224] 3.25℃ for 30min

[0225] 4.1C constant current charging to 3.65V, constant voltage charging, cut-off current 0.05C

[0226] 5.25℃ for 5 minutes

[0227] 6.1C discharge to 2.5V

[0228] 7.25℃ for 5 min

[0229] 8. The above is a charge and discharge cycle of the battery, which is repeated continuously until the battery capacity

[0230] When it decays to 80% of the initial value, the number of cycles is recorded.

[0231] 8) Capacity attenuation

[0232] The capacity retention rate at the 1000th cycle = (discharge capacity at the 1000th cycle / discharge capacity at the initial cycle) × 100%.

[0233] 9) Cycle climbing degree

[0234] Record the number of cycles in which the capacity retention rate is continuously higher than 100% during the first 3000 cycles. If the number of cycles continuously higher than 100% is ≥10, it is determined that a cycle climbing degree has occurred during the cycle process, and the maximum capacity retention rate when the capacity retention rate is higher than 100% during the cycle process is recorded. The cycle climbing degree is the maximum capacity retention rate value minus 100%. If the number of cycles continuously higher than 100% is <10, it is determined that no cycle climbing degree has occurred during the cycle process, and it is recorded as "-".

[0235] 10) Pole flexibility

[0236] At room temperature and with air humidity below 10%, cut the electrode into a shape of 5-10cm long and 2-4cm wide, fold it in half and roll it up, then use a 2Kg roller to roll it at a constant speed of 2-3m / min to observe whether the fold of the electrode is light-transmissive, and qualitatively judge the flexibility of the electrode. n-fold light transmission means: in the test of the electrode produced in the same batch, the electrode is folded back and forth at the same fold and rolled n times before it is light-transmissive. The larger the n value, the better the flexibility of the electrode.

[0237] III. Analysis of test results of various embodiments and comparative examples

[0238] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The positive electrode film parameters are shown in Table 1, and the performance test results are shown in Table 2.

[0239]

[0240] Table 2: Performance test results

[0241]

[0242] According to the above results, the positive electrode sheets in Examples 1-19 all include a positive electrode current collector and a positive electrode film layer, the positive electrode film layer is arranged on at least one side of the positive electrode current collector, the positive electrode film layer includes a first positive electrode film layer and a second positive electrode film layer, the first positive electrode film layer is located between the positive electrode current collector and the second positive electrode film layer, wherein the first positive electrode film layer contains a first positive electrode active material, and the specific surface area of ​​the first positive electrode active material is 12m 2 / g-16m 2 / g, based on the total weight of the first positive electrode active material, the carbon content of the first positive electrode active material is 1.0 wt%-1.5 wt%, the second positive electrode film layer comprises a second positive electrode active material, and the specific surface area of ​​the second positive electrode active material is 6m 2 / g-19m 2 / g, based on the total weight of the second positive electrode active material, the carbon content of the second positive electrode active material is 1.1 wt %-2.1 wt %. From the comparison between Examples 1-19 and Comparative Examples 1-3, it can be seen that the positive electrode sheets of the embodiments of the present application have good sheet flexibility.

[0243] Attached Figure 1 The microscopic morphology of the first positive electrode active material in Example 1 of the present application is shown. As can be seen from the figure, the first positive electrode active material in Example 1 of the present application comprises large particles and small particles that are evenly mixed, and the small particles densely fill the pores of the large particles, so that the first positive electrode film layer has a higher compaction density.

[0244] Attached Figure 2 The microscopic morphology of the second positive electrode active material in Example 1 of the present application is reflected. As can be seen from the figure, the particles of the second positive electrode active material in Example 1 of the present application are relatively evenly distributed, mainly medium particles, without large and small particles, and the absence of large particles can take into account the dynamics, and the absence of small particles can reduce side reactions, which is conducive to achieving a longer cycle life of the battery cell.

[0245] From the comparison between Examples 1, 4-6 and Example 17, it can be seen that when the second positive electrode active material comprises third lithium iron phosphate salt particles, and the ratio of the withheld capacity C2 of the third lithium iron phosphate salt particles at 60°C to the withheld capacity C1 of the third lithium iron phosphate salt particles at 25°C is C2 / C1≥1.02, the positive electrode plate of the embodiment of the present application has a higher compaction density, and the battery comprising the positive electrode plate of the embodiment of the present application has a longer cycle life, a lower capacity attenuation degree and a higher cycle climbing degree.

[0246] From the comparison of Examples 1, 7-8 and Examples 9-10, it can be seen that, based on the total weight of the second positive electrode film layer, when the carbon content of the second positive electrode active material is 1.2 wt%-2 wt%, the battery comprising the positive electrode sheet of the embodiment of the present application has a good balance between cycle life and gram capacity. When the carbon content of the second positive electrode active material is <1.2% (Example 9), the battery comprising the positive electrode sheet of the embodiment of the present application has a shorter cycle life. When the carbon content of the second positive electrode active material is >2% (Example 10), the battery comprising the positive electrode sheet of the embodiment of the present application has a lower gram capacity.

[0247] From the comparison of Examples 1, 13-14 and Examples 15-16, it can be seen that when the ratio W1 / W2 of the weight W1 of the first positive electrode active material to the weight W2 of the second positive electrode active material is 3:7 to 7:3, the positive electrode sheet of the embodiment of the present application has a higher compaction density, and the battery containing the positive electrode sheet of the embodiment of the present application has a higher cycle climbing degree. When W1 / W2<3:7 (Example 15), the positive electrode sheet of the embodiment of the present application has a lower compaction density. When W1 / W2>7:3 (Example 16), the battery containing the positive electrode sheet of the embodiment of the present application has a lower cycle climbing degree.

[0248] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer is arranged on at least one side of the positive electrode current collector, the positive electrode film layer comprises a first positive electrode film layer and a second positive electrode film layer, the first positive electrode film layer is located between the positive electrode current collector and the second positive electrode film layer, wherein The first positive electrode film layer comprises a first positive electrode active material, and the specific surface area of ​​the first positive electrode active material is 12 m 2 / g-16m 2 / g, based on the total weight of the first positive electrode active material, the carbon content of the first positive electrode active material is 1.0 wt %-1.5 wt %, The second positive electrode film layer comprises a second positive electrode active material, and the specific surface area of ​​the second positive electrode active material is 6 m 2 / g-19m 2 / g, based on the total weight of the second positive electrode active material, the carbon content of the second positive electrode active material is 1.1 wt%-2.1 wt%.

2. The positive electrode sheet according to claim 1, wherein the compaction density of the first positive electrode active material is 2.4-2.7 g / cm when measured under a pressure of 3 T. 3 .

3. The positive electrode plate according to claim 1 or 2, wherein the first positive electrode active material comprises first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, the first lithium iron phosphate salt particles have an average primary particle size of 50-300 nm, and the second lithium iron phosphate salt particles have an average primary particle size of 400-500 nm.

4. The positive electrode plate according to any one of claims 1-3, wherein based on the total number of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles, the number of the first lithium iron phosphate salt particles accounts for 60%-80%, and the number of the second lithium iron phosphate salt particles accounts for 20%-40%. 5 . The positive electrode sheet according to claim 1 , wherein the carbon content of the second positive electrode active material is 1.2 wt % to 2 wt % based on the total weight of the second positive electrode active material. 6 . The positive electrode sheet according to claim 1 , wherein a ratio W1 / W2 of a weight W1 of the first positive electrode active material to a weight W2 of the second positive electrode active material is 1:9 to 9:

1. 7 . The positive electrode sheet according to claim 1 , wherein a ratio W1 / W2 of a weight W1 of the first positive electrode active material to a weight W2 of the second positive electrode active material is 3:7 to 7:

3. 8 . The positive electrode sheet according to claim 1 , wherein the thickness of the first positive electrode film layer and the thickness of the second positive electrode film layer are independently 5-80 μm. 9 . A secondary battery comprising the positive electrode sheet according to claim 1 .

10. An electric device comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Positive pole piece and preparation method and application thereof

    CN113036085A

  • Positive plate and preparation method thereof, electrode assembly, battery monomer, battery and electric equipment

    CN115832182A

  • Lithium iron phosphate positive electrode slurry as well as preparation method and application thereof

    CN116613309A

  • Positive pole piece, secondary battery, battery module, battery pack and electric device

    CN117083729A

  • Lithium ion battery and manufacturing method therefor

    WO2015005228A1

Cited By

  • Positive electrode sheet, secondary battery and electric device

    EP4625515A1